Предмет: Математика,
автор: elenahromtau
5(3-2у)-4(9-у)=3(у+5)
14(2х-3)-5(х+4)=2(3х+5)+5х
9(3х-7)+3(8х-11)=3(9х+8)
6(7х-11)-13(х-6)=14(2х+1)
Ответы
Автор ответа:
0
1) 5(3 - 2у) - 4(9 - у) = 3(у + 5),
15 - 10у - 36 + 4у = 3у + 15,
-6у - 21 = 3у + 15,
-6у - 3у = 15 + 21,
-9у = 36,
у = 36 : (-9),
у = -4;
2) 14(2х - 3) - 5(х + 4) = 2(3х + 5) +5х,
28х - 42 - 5х - 20 = 6х + 10 + 5х,
23х - 62 = 11х + 10,
23х - 11х = 10 + 62,
12х = 72,
х = 72 : 12,
х = 6;
3) 9(3х - 7) + 3(8х - 11) = 3(9х + 8),
27x - 63 + 24x - 33 = 27x + 24,
51x - 96 = 27х + 24,
51х - 27х = 24 + 96,
24х = 120,
х = 120 : 24,
x = 5;
4) 6(7х - 11) - 13(х - 6) = 14(2х + 1),
42х - 66 - 13х + 78 = 28х + 14,
29х + 12 = 28х + 14,
29х - 28х = 14 - 12,
х = 2.
Похожие вопросы
Предмет: Окружающий мир,
автор: darkkeep
Предмет: Английский язык,
автор: zadinaabdulaeva
Предмет: История,
автор: mustafinasamira319
Предмет: Математика,
автор: Kiruyxa
Предмет: Биология,
автор: alexsvi